Prevalence and associated factors of opioid relapse among methadone maintenance therapy patients in Johor Bahru government health clinics, Malaysia - Mohmad, Faradia (2021)
The increasing number of opioid user and opioid overdose worldwide was quite concerning. The increment trend of annual opioid seizures reported from 2017 with 603kg to 1441kg in 2018 reflecting increase opioid use among Malaysian. National Anti-Drug Agency (NADA) reported an increasing pattern of relapse cases from 23.9% in 2015 to 30.8% of cases in 2018. As opioid relapse after detoxification was reported as one of the risk factors for opioid overdose, exploring factor contributed to relapse was crucial in reducing relapse related problem. Moreover, government have spent quite a lot for drug addiction and methadone program in Malaysia. Failing in detoxification program may impose a financial burden on the government for dealing with the drug misuse problem as well as reducing the objective of methadone treatment. This study aims to determine the prevalence of opioid relapse and the relationship of various contributing factors with opioid relapse among patients registered under the Methadone Maintenance Therapy (MMT) program in Johor Bahru Health District. A cross-sectional study was performed among patients who reached dose stabilization (eight weeks at a constant dose of methadone), comparing between relapse and nonrelapse group, involving 159 patients registered under Methadone Maintenance Therapy (MMT) Program in Health District Johor Bahru. The contributing factors studied were socio-demographic characteristics, MMT history, comorbidity, crime history, cognitive and interpersonal factors, and social-environment influence. Face to face interview based on a structured questionnaire was done. Multiple logistic regression was used to determine the predictors. A significant level was set at alpha less than 5%. The response rate was 86.9% with the majority of them were Malay, male, and Muslim. The prevalence of opioid relapse was 11.9%. Respondents with no polydrug user history (only took heroin) were more likely to have an opioid relapse as compared to polydrug users (AOR= 3.701, 95% CI= 1.182, 11.587, p=0.025). With regards to relapse risk assessment, respondents who classified as having moderate relapse risk (AOR= 5.869, 95% CI=1.524, 22.595, p=0.010) and high relapse risk (AOR=5.952, 95% CI=1.000, 35.445, p= 0.050) were about 6 times have a higher risk of having opioid relapse as compared to respondents who classified as having low relapse risk. Respondents with higher cognitive and behavioral problemsolving response scores were less likely to have an opioid relapse (AOR= 0.949, 95% CI=0.909, 0.991, p=0.008). This study revealed that one in a tenth of MMT patients reported having an opioid relapse. Non-polydrug users and higher relapse risk were positively associated with opioid relapse while patients with higher cognitive and behavioral problem solving response scores were negatively associated with opioid relapse. Efforts should be made by the policy makers and program planers to advocate relapse-free among MMT patients, taking into consideration the significant predictors. This could help spearhead the program to be, parallel with the main aim targeted by the Ministry of Health for Methadone Maintenance Therapy in Malaysia.